2021
DOI: 10.4103/ijo.ijo_1069_21
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on cataract surgical volume: A North Indian experience

Abstract: Purpose: To analyze the impact of the pandemic on trends in cataract surgical volume in 2020 in a high-volume tertiary care academic center in North India. Methods: The monthly cataract surgical volume for a large, high-volume, tertiary care academic center in North India was obtained from January 2018 through December 2020. Based on historical trends, we used time-series forecasting, probability sensitivity analysis, and linear regression models to estimate what the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Our findings are consistent with a Polish study [ 11 ]. Similarly, other countries [ [12] , [13] , [14] , [15] , [16] , [17] ] reported drastic reductions in the usual volume of cataract surgeries or ophthalmic procedures by 67 %–99 % in the early phase of the pandemic. However, the recovery of cataract surgeries was uneven across regions, independent of country income status.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our findings are consistent with a Polish study [ 11 ]. Similarly, other countries [ [12] , [13] , [14] , [15] , [16] , [17] ] reported drastic reductions in the usual volume of cataract surgeries or ophthalmic procedures by 67 %–99 % in the early phase of the pandemic. However, the recovery of cataract surgeries was uneven across regions, independent of country income status.…”
Section: Discussionmentioning
confidence: 86%
“…Due to suspension of cases during the lockdown and incoming new cases that are performed below 100 % capacity (without a simultaneous increase in resources) during the recovery phase, a substantial cataract surgical backlog is likely. A study in India [ 14 ] estimated that it would take 10 months under the ambivalent scenario to reach pre-pandemic expected cataract surgical volumes once elective surgical suspension is lifted and surgeries resume, during which there would be a collective backlog of 11 months’ worth of cases. In high income countries [ 10 , 30 ], the time estimated to revert to pre-pandemic volumes under the pessimistic scenario is shorter—approximately 6–7 months.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies about cataract surgeries in this period. [7][8][9] In this study, we aimed to compare and discuss the clinical characteristics of patients who underwent cataract surgery, which is an elective case, before and during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…6 A recent single centre study showed that there was reduction of 20% in cataract surgeries during COVID 19 due to restrictions imposed by government. 7 The ministry has suggested gradually increasing the number of cataract operations nationwide in the fiscal years 2022-2023 to 7.5 million, 9 million in 2023-2024, and 10.5 million in 2024-25, for a total of 27 million operations over the following three years. 8 In India, optometrists are the primary eye care professionals who provide comprehensive eye and visual examination that includes refraction, prescribing spectacles, detecting and diagnosing ocular diseases and referring for appropriate management.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the criteria for the referral of patients for cataract surgery to ophthalmologists have not been studied till date. Given the predicted increase in the global prevalence of age-related cataract and the growing backlog of cataract surgical cases in India, [6][7][8] the current study aimed to investigate the practice of cataract referral among Indian optometrists.…”
Section: Introductionmentioning
confidence: 99%